Health Insurance and Disclosure of Same-Sex Sexual Behaviors Among Gay and Bisexual Men in Same-Sex Relationships - Petroll, Andrew E. (LGBT Health, 2015)
Purpose: Gay and bisexual men (GBM) have poorer health outcomes than the general population. Improved health outcomes will require that GBM have access to healthcare and that healthcare providers are aware of their sexual behaviors. This study sought to examine factors associated with having health insurance and disclosure of same-sex sexual behaviors to primary care providers (PCPs) among GBM in primary same-sex relationships. Methods: We conducted an online survey of a national sample of 722 men in same-sex couples living in the United States. Logistic regression and multinomial regression models were conducted to assess whether characteristic differences existed between men who did and did not have health insurance, and between men who did and did not report that their PCP knew about their same-sex sexual activity. Results: Our national sample of same-sex partnered men identified themselves predominantly as gay and white, and most reported having an income and health insurance. Having health insurance and disclosing sexual behavior to PCPs was associated with increasing age, higher education, and higher income levels. Insurance was less prevalent among nonwhite participants and those living in the south and midwest United States. Disclosure of sexual behavior was more common in urban respondents and in the western United States. In 25% of couples, one partner was insured, while the other was not. Conclusions: Having health insurance and disclosing one's sexual behavior to PCPs was suboptimal overall and occurred in patterns likely to exacerbate health disparities among those GBM already more heavily burdened with poorer health outcomes. These factors need to be considered by PCPs and health policymakers to improve the health of GBM. Patient- and provider-targeted interventions could also improve the health outcomes of GBM.